The Role of University Teachers in the Assistance to International Students - O. P. Marinenko (Moscow Polytechnic University, 2019)
The idea of providing additional assistance and support to international students is being widely popularized in the global scientific community. This is due to the fact that the number of these students is constantly increasing and they have to encounter numerous problems. There are three main areas of international students' assistance: didactic assistance focused on the learning process; psychological assistance as the prevention and solution of psychological and emotional problems; sociocultural assistance dealing with adaptation to new environment. This article presents the results of the study directed by the following research questions: whether university teachers are involved in assisting international students, what strategies they prioritize, and what categories of teachers are more focused on providing assistance. The group survey covering 24.2% of teachers of the Interstate Educational Institution of Higher Education "Belarusian-Russian University" resulted in the following conclusions. 1. Most of university teachers are aware of international students' problems and provide them with additional assistance and support. 2. Teachers with little pedagogical experience, female respondents, and teachers without a scientific degree are more actively involved in assisting international students. 3. The most popular strategies of didactic assistance were explaining details of students' self-directed work, using lecture presentations and encouraging participation in individual consultations. 4. In order to psychologically support international students, teachers strive to tolerate their speech errors, help them in speaking and create a positive atmosphere in the class. 5. Within the framework of sociocultural assistance, teachers may give students the opportunity to present their homeland, encourage intercultural communication in seminars and workshops, and speak about the country of study.